Alcohol‐based Hand Sanitizers amid COVID‐19: Chemical Formulation, Analysis, Safety. Issue 45 (1st December 2022) - Islam, Monarul; Shahin Ahmed, Khondoker; Karim, Rezaul; Nath, Bikash Dev; Prosad Moulick, Shyama; Islam, Rashedul; Mahmudul Hassan, Sharkar Md.; Hossain, Hemayet; Moniruzzaman, Mohammad; Jahan, M. Sarwar; Ali Shaikh, Aftab; Georghiou, Paris E.
Abstract: Alcohol‐based hand sanitizers (ABHSs) containing ethanol (EtOH) or isopropyl alcohol (IPA) to inactivate microorganisms help prevent the spread of respiratory diseases. These products have become very popular during the COVID‐19 pandemic. Apart from vaccines or other preventative antiseptic measures, the majority of consumers have relied on different types of ABHSs to disinfect their hands. As a result, there has been a global rush in the demand for these ABHSs and other antiseptic hygiene products. This has resulted in the formation of many new commercial sanitizer producers. There are around fifty companies of varying sizes that have been marketing their ABHSs in Bangladesh, most of which have only been manufacturing their products for the first time since the COVID‐19 pandemic. To monitor the quality and components of these products, the Bangladesh Council of Scientific and Industrial Research (BCSIR) analyzed approximately 200 different hand sanitizer samples using GC‐FID method. All samples were alcohol‐based except for 3 which were alcohol‐free aqueous hand sanitizers. Of the supplied formulated ABHSs, 80 samples were found to contain only IPA and 54 contained only EtOH. However, 28 samples were found to be contaminated with methanol (MeOH), 7 samples contained only MeOH and 18 samples contained both EtOH and IPA. This is the first study to explore the analysis of alcohol content in formulated ABHSs and their marketing status in Bangladesh, but the findings could be of use in other jurisdictions as similar issues have been raised in many parts of the world. Abstract : Since there was no option except hand sanitizers before proper treatment of COVID, alcohol‐based hand sanitizers (ABHSs) became very popular to inactivate microorganisms and GC‐FID method is easy teachnique to determine the alcohol content in formulated products.